Vpliv hipoksije na vedenjsko termoregulacijo - laboratorijski poskusi - Golja, Petra (Medicinski razgledi, 2002)
After detection of a thermal stimulus, human beings initiate thermoregulatory behaviour in order to adjust the bodyćs temperature. If detection of thermal stimuli is impaired or altered in any way, the behavioural thermoregulatory response can be altered to such an extent that it is no longer proportional tothe thermal disturbance. Oxygen is essential for optimum functioning of the central nervous system. A lower partial pressure of oxygen in the breathing mixture (hypoxia) can be expected to affect the regulation of human body temperature. If autonomous mechanisms are also inhibited due to the expansion of the thermoregulatory nullzone, it is possible for a person at high altitudeto be more prone to hypothermia, without being aware of it. A shift ofthe core temperature towards hypothermia may become critical in the absence of conscious detection, because the person will be unable to react appropriately in order to prevent further cooling of the body. Due to an inappropriate behavioural response to thermal disturbances in a hypoxic environment, the body may also be more prone to cold injury - e.g. freezing and non-freezing cold injury. (Abstract truncated at 2000 characters)
Keywords: hipoksija; termoregulacija; mraz; ozebline